What is the impact of multidisciplinary team simulation training on team performance and efficiency of patient care? An integrative review. Issue 1 (February 2016) - Murphy, Margaret; Curtis, Kate; McCloughen, Andrea
Summary: Background: In hospital emergencies require a structured team approach to facilitate simultaneous input into immediate resuscitation, stabilisation and prioritisation of care. Efforts to improve teamwork in the health care context include multidisciplinary simulation-based resuscitation team training, yet there is limited evidence demonstrating the value of these programmes. 1 We aimed to determine the current state of knowledge about the key components and impacts of multidisciplinary simulation-based resuscitation team training by conducting an integrative review of the literature. Methods: A systematic search using electronic (three databases) and hand searching methods for primary research published between 1980 and 2014 was undertaken; followed by a rigorous screening and quality appraisal process. The included articles were assessed for similarities and differences; the content was grouped and synthesised to form three main categories of findings. Results: Eleven primary research articles representing a variety of simulation-based resuscitation team training were included. Five studies involved trauma teams; two described resuscitation teams in the context of intensive care and operating theatres and one focused on the anaesthetic team. Simulation is an effective method to train resuscitation teams in the management of crisis scenarios and has the potential to improve team performance in the areas of communication, teamwork and leadership. Conclusion: Team training improves the performance of the resuscitation team in simulated emergency scenarios. However, the transferability of educational outcomes to the clinical setting needs to be more clearly demonstrated.